New Types of β Generalized and β Separate Axioms for Topological Spaces - Rukaia M. Rashed (Journal of Pure & Applied Sciences, 2020)
The aim of this paper is to present and study some new types of separation axioms called - generalized separation axioms, termed by generalized - and generalized - . The axioms were presented by using generalized - open sets in topological spaces according to Ganster and Steiner. The study Showed the connections, properties and characteristics between these axioms provided with examples and theorems.